EVALUASI ANALITIK POCT METODE GLUCOSE DEHYDROGENASE PARAMETER GLUKOSA PADA SPESEIMEN SERUM DAN PLASMA EDTA - Suryanata Kesuma; Didi Irwadi; Nia Ardelia (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2021)
Diabetes is a non-communicable disease that can be prevented and detected as early as possible by routine glucose checks. Point Of Care Testing (POCT) as a diabetes test screening tool is widely used by health care institutions and is even used independently by the wider community. Blood glucose can be measured by serum, plasma, and whole blood specimens. The standard specimen for glucose measurement using POCT is whole blood. Based on the author's survey, the use of the POCT tool in several health care institutions was not following the insert of the tool kit, one of which was the type of specimen used. Many laboratories use EDTA serum and plasma specimens for glucose testing using the POCT device. There are many methods used in the POCT tool, one of these methods is the glucose dehydrogenase method. Therefore analytic evaluation is necessary to ensure the accuracy and accuracy of laboratory examination results in glucose examination. This type of research is the analytical method with a comparative design. The data was collected using the total sampling method. The data is reported using Microsoft Excel and SPSS applications. The number of samples for analytic evaluation was 40 samples. Based on the results of tests performed in duplicate, there were clinical differences in glucose values using serum and plasma EDTA samples so that the use of these samples was not suitable for use for diagnostic purposes using the POCT glucose dehydrogenase method. There was a statistical difference in serum glucose and plasma EDTA against whole blood that was examined using the POCT glucose dehydrogenase method with a correlation value (R) of 0.9722 and 0.9695.